2019
DOI: 10.1186/s12967-019-2044-7
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma activates AKT signaling to promote wound healing in a mouse model of radiation-induced skin injury

Abstract: Background The skin is impacted by every form of external radiation therapy. However, effective therapeutic options for severe, acute radiation-induced skin reactions are limited. Although platelet-rich plasma (PRP) is known to improve cutaneous wound healing, its effects in the context of high-dose irradiation are still poorly understood. Methods We investigated the regenerative functions of PRP by subjecting the dorsal skin of mice to local irradiation (40 Gy) and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…The present study identified the AKT pathway as the main signaling pathway through which CGF exerts its immunoregulatory effects. PRP also exerts a regenerative effect via the AKT pathway [ 38 , 39 ], which supports our results. A variety of growth factors that are present in CGF extract can induce activation of AKT signaling.…”
Section: Discussionsupporting
confidence: 90%
“…The present study identified the AKT pathway as the main signaling pathway through which CGF exerts its immunoregulatory effects. PRP also exerts a regenerative effect via the AKT pathway [ 38 , 39 ], which supports our results. A variety of growth factors that are present in CGF extract can induce activation of AKT signaling.…”
Section: Discussionsupporting
confidence: 90%
“…* P < 0:05 by a one-way ANOVA followed by Fisher's protected least post hoc test. 6 Mediators of Inflammation healing in numerous cell lines, including epithelial cells, keratinocyte, and cancer cells [23][24][25][26][27][28]. To clarify the growth-promoting mechanism of epithelial cells, the status of MAPK signaling was assessed.…”
Section: Poly P Improved the Wound Healing Of Intestinalmentioning
confidence: 99%
“…As revealed from the results, PRP enhances cell function via AKT signaling, thereby facilitating the regeneration of irradiated skin. The ability of PRP to promote skin healing is worth conducting clinical research and application [ 69 ].…”
Section: Therapymentioning
confidence: 99%